Pulse reflection sites and effective length of the arterial system - Campbell, K B; Lee, L C; Frasch, H F; Noordergraaf, A (The American journal of physiology, 1989)
The concept of effective length (L) of the arterial system implies that it may be represented by a single viscoelastic tube terminated by an impedance, creating a single reflection site. Although the concept is straightforward, investigators for years have been unable to agree on the value of L. Proposed values range from a few millimeters to a few meters, confounding the identification of arterial reflection sites. This report shows analytically and illustrates with experimental data that the determination of the effective length leaves room for an infinite number of exact solutions for L and the corresponding terminal impedance if the input impedance of the tube is to match the measured input impedance of an arterial system. None of the possible values of L needs to bear any relationship to actual reflection sites.